LIBER-EBLIDA Digitisation Workshop - Ayris, Paul (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2008)
95 participants from 23 countries attended a Workshop on the Digitisation of Library Material in Europe, from 24 to 26 October 2007 in the Royal Library, Copenhagen, Denmark. The Workshop was jointly organised by LIBER and EBLIDA. In a full report on the Workshop on the JISC website, the JISC highlighted that ‘high on the agenda were moves towards a European Digital Library – the delivery of integrated access to the digitised collections of libraries, archives and museums across the EU.’ At a global level, this was indeed one of the main aims of the Workshop. As the Chair of the breakout groups, and the final session of the Workshop, I gave an interview for the JISC immediately after the final session where I looked at what I thought were some of the issues to be identified by the Workshop. The purpose of this paper is to describe some of these issues in a little more detail and outline what work LIBER and EBLIDA have undertaken in the wake of the significant momentum which the Workshop has engendered for European digitisation activity.